2020
DOI: 10.1080/23311916.2020.1790980
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of two steps on the performance and longitudinal stability of a mono-hull high-speed craft

Abstract: Transverse steps in modern high-speed craft can increase the longitudinal stability in addition to reducing frictional resistance. The porpoising instability can also be avoided by selecting the appropriate location and height of the transverse step. In the current paper, a non-step and a double-step model are investigated. The primary purpose of the present study is to examine the impact of second step on the stability and performance of the craft. Both models are generally identical. They are prismatic with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Te authors have previously tested a double-stepped confguration of the parent model in a towing tank [35]. Te four design parameters for steps locations and angles in double-stepped hulls are shown in Figure 2.…”
Section: Physics Of the Problem And Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Te authors have previously tested a double-stepped confguration of the parent model in a towing tank [35]. Te four design parameters for steps locations and angles in double-stepped hulls are shown in Figure 2.…”
Section: Physics Of the Problem And Methodologymentioning
confidence: 99%
“…Furthermore, Sajedi and Ghadimi [35] conducted other experiments to investigate the performance of a doublestepped hull with steps at 15% and 30% of vessel length to the stern in Froude numbers ranging from 0.43 to 3.87. Te step location efects in double-stepped hulls with transverse steps at speeds of 10 and 12 m/s were also numerically investigated by Ghadimi et al [36] and validated by some experimental tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different inputs must be considered in the computational process. The governing equations for the resistance are given in equations ( 10)- (12). These equations are a combination of coefficients of friction resistance and total strength.…”
Section: Experimental Uncertaintymentioning
confidence: 99%
“…Concerning the double-stepped hulls, Lee et al 11 determined the role of step height in the performance of double-step hulls by testing seven different hull configurations. Sajedi and Ghadimi 12 also extended their experimental investigation to the double-step hulls. Their measurements demonstrated that, in addition to promoting longitudinal stability, the double steps are also beneficial in the pre-planing regime by reducing the resistance.…”
Section: Introductionmentioning
confidence: 99%